2014
DOI: 10.1002/jhbp.149
|View full text |Cite
|
Sign up to set email alerts
|

Indication for neoadjuvant chemotherapy in patients with colorectal liver metastases based on a nomogram that predicts disease-free survival

Abstract: The nomogram validation was shown to be moderately predictive. PHC decreased the performance of the nomogram and might produce no DFS benefit in patients with low recurrent risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
5
16
0
Order By: Relevance
“…Regarding the independent prognostic factors in the nomograms, non-R0 resection and primary lymph node metastasis were found to be associated with poor OS and PFS, which was consistent with the findings of previous studies (7,8,24). Some nomograms have been developed to predict individual survival probabilities for CRLM patients receiving NAC (7,8,11), but the present nomograms have some unique features. First, TRG was incorporated into the nomogram for predicting PFS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the independent prognostic factors in the nomograms, non-R0 resection and primary lymph node metastasis were found to be associated with poor OS and PFS, which was consistent with the findings of previous studies (7,8,24). Some nomograms have been developed to predict individual survival probabilities for CRLM patients receiving NAC (7,8,11), but the present nomograms have some unique features. First, TRG was incorporated into the nomogram for predicting PFS.…”
Section: Discussionsupporting
confidence: 88%
“…Nomograms provide a graphical representation of a predictive model and are used to generate a numerical probability of a clinical event and are thus helpful for formulating reasonable clinical strategies early in CRLM patient management. However, only a few studies (7,8,11) have developed a nomogram for CRLM patients who received NAC followed by hepatic resection, and the previous nomograms are lacking in several ways. First, these nomograms did not consider the influence of NAC-related factors [e.g., tumour regression grade (TRG), NAC toxicity] or preoperative testing markers [e.g., gamma-glutamyl transpeptidase (GGT), D-dimer] on prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to those aiming at early stages that have shown higher accuracy, nomograms for recurrence after curative surgery in CRLM patients with usability and accuracy have not been satisfactory due to the complexity of CRLMs [ 7 , 17 , 28 , 48 , 49 ]. Our nomogram yielded an AUC of 0.866 and 0.792 for internal and external validation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the relationship between Beppu's nomogram score and DFS. For example, Okuno et al (21) reported that Beppu's nomogram score is a marker of poor DFS. Two hundred and thirty-four patients with colorectal liver metastases who underwent hepatic resection were evaluated using Beppu's nomogram.…”
Section: Discussionmentioning
confidence: 99%